PENGARUH UNCAC TERHADAP PENGESAHAN UNDANG-UNDANG NO 5 TAHUN 2023 TENTANG EKSTRADISI BURONAN ANTARA INDONESIA DAN SINGAPURA - Sari, Ade Wulan; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study explained the internal and external factors behind the ratification of the Extradition Treaty between Indonesia and Singapore, which had been planned by the government since 1998. UNCAC serves as one of the external factors influencing the ratification of the treaty. However, aside from UNCAC, internal factors from each country also played a role in the ratification process. This research used qualitative methodology, with data collection techniques implemented through interview and literature studies sourced from books, journals, articles, and websites. This research utilized the theory of international interest and focused on the period between 2019-2023. The findings of this paper presented the external and internal factors influencing the ratification of the treaty. External factors such as UNCAC as a guideline for the ratification, and interdependence among states. Internal factors such as national interests including national security of Indonesia, Flight Information Region (FIR), and Defense Cooperation Agreement (DCA).